Hypertext as a Basis for Constructing Language Environment in the Postmodern Culture Гипертекст как основа построения языковой среды в культуре постмодерна Гіпертекст як основа побудови мовного середовища у культурі постмодерну - O. E. Vysotska (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
The main components of the construction of the language environment in the Postmodern culture are examined. The forms of communication evolution from text to hypertext are disclosed. It is proved that hypertext is a non-linear structure of the language of modern virtual communication and determines the nature of the relationship in postmodern culture. Рассмотрены основные составляющие построения языковой среды в культуре постмодерна. Раскрыт характер эволюции форм коммуникации от текста к гипертексту. Доказывается, что гипертекст является нелинейной сетевой языковой структурой современных виртуальных средств коммуникации и определяет характер отношений в
культуре постмодерна. Розглянуто основні складові гіпертексту як основи побудови мовного середовища в культурі постмодерну. Розкрито характер еволюції форм комунікації від тексту до гіпертексту. Доводиться, що гіпертекст є нелінійною мережною мовною структурою сучасних віртуальних засобів комунікації і визначає характер відносин у культурі постмодерну.